Pemetaan Awal Ditribusi Populasi Tanaman Sukun (Artocarpus altilis (Parkinson) Fosberg 1941) di Pulau Ternate - Suparman R; Zulkifli Ahmad (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2015)
The objective of the research is to provide a comprehensive map of population, distribution and detail number of Sukun/Breadfruit (Artocarpus altilis (Parkinson) Fosberg in Ternate Island. The main methode is explorer survey and decomentation the location specifically include number of trees and location in Global Position System. The location is limited for accessible location only. The result reveal that Breadfruit population are 370 threes and it is spreaded in 23 district with 55 pointpopulation. The most abundant distric is Gambesi with 48 threes of sukun in total and 31 threes per km2 in density. Meanwhile, the densest distric is Ngade district that with 85 threes per km2 in density.Keywords: Artocarpus altilis (Parkinson) Fosberg, mapping, Ternate